ANALYSIS OF HUMAN PERFORMANCE IMPROVEMENT FACTORS BETWEEN FRONTLINE HOTEL SERVICES - Indah Wahyu Utami; Ilham Sentosa; Sharina Osman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Tourism makes a significant contribution to Indonesia's economic growth. The hospitality industry provides significant support to the tourism industry. The hospitality industry services is an industry engaged in services and has high competitiveness. One of the supporting factors in the hospitality industry is the role of human resources. Human resources that support the continuity of service activities in the hotel. Hotel management, especially in the city of Surakarta, Central Java, Indonesia continues to develop strategies for the management of services to consumers. One of them improves the performance of employees on the front line. Improvements in the reward system, task commitment, career development, and role ambiguity, will affect motivation and empowerment to improve front-line hotel employees' performance in Surakarta City.